1998
DOI: 10.1038/sj.onc.1202027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features of a new human lymphoma cell line carrying both BCL2 and BCL6 gene rearrangements

Abstract: Chromosomal translocations and/or their molecular equivalents involving the BCL6 gene on 3q27 band have been suggested to be involved in the development of nonHodgkin's lymphoma of B-cell type (B-NHL). The rearrangement of BCL6 sometimes coexists with other translocations speci®c to B-NHL. Here, we report a novel B-cell lymphoma cell line, YM, established from a patient with di use large cell lymphoma. The YM cells expressed B-cell-associated antigens in addition to md/k monoclonal immunoglobulin. Southern blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…1012 had t(3;16) as the sole chromosome abnormality, indicating that the translocation was the primary genetic abnormality in this particular case (Ichinohasama et al, 1998). In contrast, YM cells carried a t(2;18)(p11;q21) leading to the fusion between BCL2 and the IG k-light chain gene (Yonetani et al, 1998), raising the possibility that the t(3;16) was a secondary change that developed in a prelymphomatous B-cell with BCL2 translocation and was related to progression to¯orid lymphoma. However, recombination activation genes (RAG) 1/2 have been shown to be reactivated in the germinal center (Han et al, 1997), therefore, oncogene/IG translocation mediated by V(D)J recombination may not be restricted to B-cell precursors in the bone marrow but can occur in the peripheral lymphoid organs.…”
Section: Of Three Independent Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…1012 had t(3;16) as the sole chromosome abnormality, indicating that the translocation was the primary genetic abnormality in this particular case (Ichinohasama et al, 1998). In contrast, YM cells carried a t(2;18)(p11;q21) leading to the fusion between BCL2 and the IG k-light chain gene (Yonetani et al, 1998), raising the possibility that the t(3;16) was a secondary change that developed in a prelymphomatous B-cell with BCL2 translocation and was related to progression to¯orid lymphoma. However, recombination activation genes (RAG) 1/2 have been shown to be reactivated in the germinal center (Han et al, 1997), therefore, oncogene/IG translocation mediated by V(D)J recombination may not be restricted to B-cell precursors in the bone marrow but can occur in the peripheral lymphoid organs.…”
Section: Of Three Independent Experimentsmentioning
confidence: 99%
“…Cytogenetic and molecular analysis of YM cells revealed that the cells carried t(3;16)(q27;p11) and t(2;18)(p11;q21) involving BCL6 and BCL2, respectively (Yonetani et al, 1998 (Ichinohasama et al, 1998). The cell lines used in the present study were cultured in RPMI 1640 medium supplemented with 10% fetal calf serum (FCS) under the standard culture conditions.…”
Section: Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 DNA was digested with add(5)(p12),del(6)(q13q25),der(9)t(4;9)(q21;p22)del(4)(q31q33),der(10)t(5;10)(p12;q11), der(14)t(2;14)(q31;q32),der(18)t(14;18)(q32;q21),+22,der (22) der(9)del(9)(p22)t(1;9)(q13;q34),−13,−14 [30] 22 DLBCL PB 49,XX,+X,t(1;3)(p34;q27),der(6)t(6;7)(q13;q22),der (7) 32 LDI-PCR from the IGHJ segments and from 5Ј S to amplify the derivative partner chromosome was performed as described. 35,36 LDI-PCR products were cloned into pTOPO (Invitrogen, San Diego, CA, USA) and sequenced.…”
Section: Southern Blot and Igh Ldi-pcr To Detect Bcl6 Rearrangementsmentioning
confidence: 99%